Circadian phase inversion causes insulin resistance in a rat model of night work and jet lag - Anhui Wang; Ewout Foppen; Valentina S. Rumanova; Tess Kool; Andries Kalsbeek; Dirk J. Stenvers (Scientific Reports)
Abstract Shift workers have an increased risk to develop type 2 diabetes. We aimed to investigate the underlying mechanisms and the role of the timing of food intake by subjecting rats to an acute phase inversion of the light/dark (L/D) cycle. In the first experiment, with food available ad libitum, male Wistar rats were implanted with jugular vein catheters and intravenous glucose tolerance tests were performed at either ZT2 or ZT14. Three days after the 12 h phase shift, these glucose tolerance tests were repeated. In the second experiment, rats were housed in metabolic cages for the continuous measurement of multiple behavioral and metabolic parameters after the 12 h phase shift, food was available ad libitum or restricted to the light or dark period. The daily rhythm of glucose tolerance, and the peak and trough corticosterone levels, adapted within three days after exposure to the inverted L/D cycle. However, phase inversion caused insulin resistance at the onset of the active phase. Under ad libitum feeding conditions, the daily rhythms of locomotor activity and energy expenditure adapted faster to the inverted L/D cycle compared to the other behavioral rhythms measured. Food restriction to the dark period facilitated behavioral adaptation to the new circadian phase.